Correlation between Tertiary Education Graduates by Field of Study and Economic Development—An analysis of European countries - Jarmila Hojs Potočnik; Polona Tominc (Naše gospodarstvo/Our economy, 2013)
In this paper the correlation between the structure of graduates by study fields (using ISCED 1997 classification) and real GDP per capita is analyzed for the 25 countries of the European Union, Iceland, Norway, and Switzerland. Although the relationship between education and economic development has been the topic of numero- us studies, results are often contradictory, and only a few studies have analyzed the structure of graduates by study fields of education. Our research results suggest that the structure of graduates by study fields correlates with the GDP per capita, where some negative and some positive correlations are identified.